Chilton Asian diagnostic service - Acura Honda (Thomson/Delmar Learning, 2007)
For Asian Vehicles 1995-2005, the Chilton 2006 Asian Diagnostic Service Manual, Volume I provides technicians with the critical diagnostic information they need to accurately identify and solve engine performance problems. Clear explanations, specifications and illustrations help technicians diagnose second generation on-board diagnostic (OBD-II) systems. Chilton Diagnostic Service Manuals, when used with an engine analyzer, scan tool or lab scope, allow diagnosticians to understand functions of engine performance components and systems, simplify testing procedures and diagnose trouble codes